Lifestyle Pathways Affecting Children's Mental Health in Japan during the COVID-19 Pandemic - Satomi Sawa; Akihito Hagihara (MDPI AG, 2023)
The recent prolonged COVID-19 pandemic has worsened the daily lives of preschoolers and elementary school children worldwide. Although these changes may have affected their mental health, the full picture still remains unknown. Since March 2020, Japan has intermittently experienced several COVID-19 waves. This survey was conducted between February and March 2022. In this study, we investigated the pathways by which specific lifestyle factors (such as exercise, sleep, diet, and life skills) affect physical/psychosocial health (PPH) in 1183 preschoolers (3-5 years old) and 3156 elementary school children (6-11 years old) in Toyama Prefecture, Japan. These pathways were examined using a path analysis. Consequently, "life skills" was found to be the factor most strongly associated with PPH in both preschoolers and elementary school children (p < 0.001). Furthermore, it was associated with the physical activity score and with PPH via physical activity. Moreover, both boys' and girls' mental health declined with age among elementary school children (p < 0.001). The results of the current study may be helpful for early interventions (around the start of elementary school) at home and at school to improve children's mental health during the COVID-19 pandemic.